Categorías de corrosividad de la ciudad de trujillo-perú 2015/2016, para el aluminio y cobre electrolítico - Hualcas Falen, Maria Fernanda (2017)
In this research the category of corrosivity of the atmosphere of the city of Trujillo on copper and aluminum in the period 2015/2016 was determined. The corrosion rates of these metals were also monitored in quarterly periods. For this purpose and using the standards ISO 9223, ISO 9226, ISO 8407 and complementary; We selected 03 sites to install an equal number of frames containing flat and spiral copper and aluminum samples; These chosen places were the campus of the university city of the UNT (3.85 km distance to the sea), the roof of a housing of the urbanization San Nicolás (5.09 km of distance to the sea) and the roof of a housing of the urbanization San Isidro (4.75 km away to the sea). From the results obtained it is concluded that the corrosion rates for copper in the form of plates 2.8 to 4.1 μm / year, for copper in the form of a spiral is of 8.8 to 11.1 μm / year, for the aluminum in the form of plate 9.9 a 20.5 gr / m2.year and for aluminum in spiral form 7.8 to 11.2 gr / m2.year. It is observed that the corrosion rates of both metals decrease almost linearly in the evaluated periods. From these final results it is concluded that the city of Trujillo has a category of corrosiveness from C4 to CX for copper (high / extreme corrosivity) and from C5 to CX for aluminum (very high / extreme corrosivity). So it could be said that the atmosphere of the city of Trujillo is extremely corrosive to copper and aluminum so we must protect them properly.